Human Security and Olongapo Residents’ Nostalgia for the US Subic Base - See, Karl Gerrard (Archīum Ateneo, 2022)
Olongapo City was economically dependent on the US naval station in Subic from the postwar years until 1991 when the Philippine Senate decided to remove it without local consultation. Thisarticle aims to fill in gaps in the overseas US basing literature by exploring grassroots sentiments in Olongapo and the reasons behind them. Theinterviews and survey show that many residents are nostalgic about Subic Base and amenable to its hypothetical return to the city. Factors behind this nostalgia are stunted economic growth, adjustments to post-base life, American ties, security concerns, and disagreement with government goals.KEYWORDS: US BASES • OLONGAPO CITY • MILITARY BASES • PUBLIC OPINION • HUMAN SECURITY